Comparative Study on the Luminescence Efficiency of Sm3+-Doped MeMoO4 (Me=Ba, Sr,Ca, and Mg) Phosphors - He, Hai- Yan (Micro and Nanosystems, 2014)
Sm-doped MeMoO4 (Me=Ba, Sr, Ca, and Mg) nanophosphors were fabricated with a sol-gel method and studied for their microstructure and photoluminescence. The matrices of the doped MgMoO4 and BaMoO4 powders show very weak blue emission, but the matrices of the doped MgMoO4 . and BaMoO4 powders show relative strong emission. The Sm3+ cation in all matrices shows very strong red emission that is more red compared with usually reported orange-red emission. Significantly, the photoluminescence efficiency of Sm3+ in SrMoO4 was largest.
Keywords: nanocrystalline materials